Upaya Meningkatkan Hasil Belajar Peserta Didik pada Tema Makanan Sehat Melalui Metode Genius Learning di Kelas V SDN 215/X Sungai Toman Semester Ganjil Tahun Ajaran 2022/2023 - Suwaibah Suwaibah (Departement of Mathematics Education, 2022)
This research is motivated by the students' thematic learning outcomes which are still low and there is a need for corrective action. The purpose of this study is to obtain information and discuss efforts to improve student learning outcomes on the theme of healthy food through the genius learning method in class V SDN 215/X Sungai Toman odd semester of the 2022/2023 academic year. This research is a classroom action research which consists of two cycles and each cycle has two meetings. Each cycle follows four stages, namely planning, implementing, observing, and reflecting. This research was carried out at SDN 215/X Sungai Toman in the odd semester of the 2022/2023 school year with a total of 20 class V students as subjects. Data collection techniques using tests, observations, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that the genius learning method can improve student learning outcomes on the theme of healthy food in class V SDN 215/X Sungai Toman in the odd semester of the 2022/2023 school year by giving bonus points to students. The increase in learning outcomes can be seen in the percentage of students' mastery learning in cycle I by 65% ​​and increased in cycle II by 85%